A Comparative Study on the Validity of Financial Transactions by Children in Iranian Contemporary Jurisprudence and Law - Muhammad Rasul blacksmiths; Ahmad Saberi Majd (پژوهش‌های فقهی مسائل مستحدثه)
The practice of buying and selling by children, characterized as a financial transaction based on intention and discretion, has presented a challenge for Islamic and Iranian jurists. The research aims to investigate and evaluate various perspectives regarding the validity or invalidity of such transactions, with the goal of reaching a balanced viewpoint. The research adopts a descriptive-analytical approach and relies on library resources for data collection. Notably, renowned Imamiyyah and Shafi'i jurists have deemed the financial transactions by children to be invalid. Conversely, some scholars argue for its validity despite factors such as the child's age or the transaction's low value. A middle-ground perspective suggests that the transactions by a child is not categorically invalid but requires permission, a standpoint supported by certain jurists from the Imamiyyah and Sunni schools. Additionally, this view finds support in Article 1211 of the Iranian Civil Code. Some jurists have also shown inclination towards this middle-ground perspective. The research findings highlight the importance of not only obtaining the guardian's permission but also considering the child's well-being and development.Received: 2023 Jul 14  |   Recieved in revised form: 2023 Aug 17   |   Accepted: 2023 Oct 7   |   Published: 2023 Oct 23